Force protection in contingency operations: an evaluation of temperature monitoring in Sierra Leone. Issue 3 (9th February 2015) - Cole, Catherine; Turnbull, C; Eardley, W; Hunt, P
Abstract : Objectives: The deployment of the UK-led Joint Inter-Agency Taskforce to Sierra Leone in September 2014 brought the era of contingency operations into focus. Daily health screening of such deployed personnel forms a key element of medical force protection. We have performed a service evaluation of an existing screening programme and detail the comparison of the two thermometers used in this role. Methods: Data from the existing screening programme were used to inform a sample size required to enable statistically and clinically significant differences to be detected between the two interchangeably used thermometer systems in use. A prospective service evaluation on these devices was then carried out over a 10-day period and the data analysed by parametric tools. 10 personnel had their temperature recorded by both devices at the same time by a single operator every day. Results: For the screened population, a mean temperature of 36.55°C and SD of 0.32°C was revealed. Powered to 80% with a two-tailed α of 0.05, the evaluation of the two thermometers revealed no significant difference between recordings taken with either device (p=0.115). The low SD meant that a pyrexial patient (>37.5°C) would require a recording over 3 SD from the population mean. Discussion: Evaluations of medical force protection will carry increasing consequence as the UK deploy on short notice operations to regions of considerable endemic threat. Presence of pyrexia is a key early indicator of illness affecting deployed personnel, and two different thermometer types are provided for this function. We have shown for the first time with statistical and clinical significance that the two thermometers used in contingency force protection are interchangeable. The narrow variance is reassuring and confirms that the chosen trigger (>37.5°C) would warrant further investigation in the pyrexial patient.